Validitas dan Praktikalitas Pengembangan Media Video Digital KineMaster pada Pembelajaran PPKn di Kelas IV - Ega Meylinda; Reinita (Elementary Teacher Education Program, Majalengka University, 2023)
The research was motivated by the lack of attractive media used, as well as the lack of teacher skills in using digital-based media in learning activities. This results in students having difficulty understanding lessons and often feeling bored and lacking motivation to learn. This research aims to produce KineMaster digital video media using the PBL model regarding Pancasila and Citizenship Education in Class IV Elementary School where learning is valid, practical, and efficient. The research carried out is Research & Development. This development uses the ADDIE model, namely analysis, design, development, implementation, and evaluation. The research was conducted at SDN 02 Kubang, SDN 07 Kubang, SDN 05 Kubang, and SDN 06 Kubang. Product testing is carried out by one media expert, one language expert, one material expert, teacher responses, and student responses. The results of the research show that learning media has a material value of 93.75 in the very valid category, a media value of 93.75 in the very valid category, and a linguistic value of 87.5 which is considered very valid. The teacher response results were 97.91 in the very practical category and the student response results were 96.41 in the very practical category. So it is concluded that the learning media in the form of KineMaster digital videos for PPKn learning in class IV elementary school is declared valid and practical